Identification of Campylobacter jejuni Using Polymerase Chain Reaction Method - Liza Angeliya; Ruri Rumpaka Kurdiwa (Jurnal Sain Veteriner, 2013)
Abstract Campylobacter jejuni is a curved-rod shaped bacteria, non-spore, microaerophilic Gram-negative and motile. It is commonly found in the feces of animals. They grow at a temperature of 37-42° C and are zoonotic causing a disease called campylobacteriosis. Campylobacter jejuni naturally presents in the chicken digestive tract and does not cause any diseases. However, chicken carcasses contaminated with this bacteria are closely related to the the incidence of campylobacteriosis in humans. Cases of human campylobacteriosis primarily caused by Campylobacter jejuni contamination on chicken carcasses. During the cutting process, Campylobacter jejuni will be able to spread to the chicken carcasses. Alternative approach for detecting Campylobacter jejuni contamination of chicken products is by using polymerase chain reaction (PCR) method. Therefore, to determine diagnosis of animal diseases in relation to the veterinary public health due to Campylobacter jejuni is by applying PCR with forward primer: 5'-TGACGCTAGTGTTGTAGGAG-3 and reverse primer: 5'-CCATCATCGCTAAGTGCAAC-3'. The PCR primers can amplify DNA Campylobacter jejuni as long as 402 bp. The PCR method is a molecular laboratory approach which is sensitive, specific, rapid and accurate for determining diagnosis of campylobacteriosis.